Development of Digital Tractive Transducer - Soyoye, Babatunde Oluwamayokun; Tehinse, Taiye Olaoluwa (Journal of Advanced Industrial Technology and Application, 2022)
Construction equipment, agricultural tractors and cross-country vehicles can only perform their given tasks when tyre matches the vehicle design, the vehicle weight and the ground on which they operate. This Research involves the design and fabrication of a digital tractive transducer to measure the effects of press wheel vertical force on the germination rate of grain crops. Design criteria, calculations and analysis of various components of the transducer were critically carried out, and then used to design, fabricate and assemble the digital tractive transducer. The effect of press wheel vertical force on seed germination showed that the crops germinated well at low press wheel loads, while high press wheel loads adversely affected the percentage germination of the crops. Maize and soybean had increasing percentage germination trends between no load and 60 N load, where any press wheel load of more than 60 N greatly affected their germination rates. For cowpea, it is better planted with no additional loads on the press wheel because the highest percentage germination was recorded at no load.